INDONESIA-MALAYSIA-THAILAND GROWTH TRIANGLE (IMT-GT) AGREEMENT RELATED TO TOURISM DEVELOPMENT ASPECT IN ACEH, A STUDY FROM LAW OF TREATY PERSPECTIVE - Rafdi Siddik; M. Putra Iqbal (Fakultas Hukum Universitas Syiah Kuala, 2017)
Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) subregional economic cooperation program was established in 1993 in Langkawi, Malaysia, through the signing of “1st Agreed Minutes” document with purposes to accelerating the economic transformation of the member states and provinces in the three countries. Aceh is a part of subregion that involve in this coorperation and tourism law in Aceh (Qanun No.8 of 2013) is the result of this agreement. However, There is a lot of shortcoming in this Qanun No.18 of 2013. The purpose of this thesis to understand Aceh local government harmonize Tourism law in Aceh with the IMT-GT Agreement and also to understand the legal status of Indonesia-Malaysia-Thailand Growth Triangle Agreement based on law of treaty. This research uses empirical normative research. The data in this study were obtained through the research libraries to acquire secondary data by way of studying the legislation, books, the internet and other scholarly works related to the problems of the research and fieldwork conducted for obtaining primary data by interviewing respondents or informants. The results showed that Tourism law in Aceh (Qanun Aceh No.8 of 2013) should be review or revised by Aceh Government to harmonize this law with this Agreed Minutes of IMT-GT agreement related to tourism aspect that explain to develop Port connectivity, Air Linkages and also Medical Tourism that also a part of IMT-GT Agreement Purposes to developt Tourism aspect in Aceh as Indonesia region that include in IMT-GT Agreement. Based on Qatar v Bahrain Case, After examining the 1990 the Court observes that they are not a simple record of a meeting, similar to those drawn up within the framework of the Tripartite Committee; they do not merely give an account of discussions and summarize points of agreement and disagreement. They enumerate the commitments to which the Parties have consented. They thus create rights and obligations in international law for the Parties. They constitute an international agreement. Thus, based on this cases, IMT-GT Agreement related to tourism aspect (1st Agreed Minutes, 2nd Agreed Minutes, 3rd Agreed Minutes) catagorized as a treaty. The Government of Aceh should revise Qanun No. 8 of 2013 on tourism and review the things what are the tourism related that should be added on the qanun. So the rules regarding tourism in aceh would be more specific. And also look back at the IMT-GT Agreement to harmonize tourism law in Aceh. The Government of Aceh also have much to learn in making international agreements (Treaty) from the Central Government which is more experienced in the making treaties. And in the process learned the government of Aceh should be plenty involving the Central Government in making treaties as regulated in the law No. 24 of 2000 on treaties.